KONSEP PENDIDIKAN KARAKTER MENURUT AL-GHAZALI DALAM KITAB AYYUHA AL-WALAD - Abi Iman Tohidi (Pascasarjana IAIN Syekh Nurjati Cirebon, 2017)
This research is based on writer’s curiosity about the character education has not been fully understood by the learner’s and has not yet become the main guidelines and has not been fully applied in the world of education in Indonesia, especially the character education contained in the book ayyuhā al walad works al-imam Ghazali. The purpose of this study is to describe (1) how is the Concept of Education Character in Islam, (2) how is the concept of Education Character of Ghazzali in the book of ayyuhā al-walad and (3) How is Education Character method according to al-Ghazali in the book ayyuhā al-walad. This research is a library (library research), with the object of research the book Ayyuhal-Walad and supported by several other books. The approach used in this study is a philosophical approach. While the analysis of data using content analysis (content analysis). With the focus of the study discussed in this study is the concept of character education according to al-Ghazali based on the book Ayyuhal-walad.Penelitian ini dilatar belakangi oleh rasa penasaran penulis tentang pendidikan karakter yang selama ini belum difahami sepenuhnya oleh peserta didik dan belum sepenuhnya menjadi pedoman utama serta belum sepenuhnya diterapkan dalam dunia pendidikan di Indonesia, khususnya pendidikan karakter yang terkandung dalam kitab ayyuhal-walad karya imam al-Ghazāli. Tujuan penelitian ini adalah untuk menjelaskan (1) bagaimana konsep pendidikan karakter menurut Islam, (2) bagaimana konsep pendidikan karakter menurut Al-Ghazali dalam kitab Ayyuhā al-walad dan (3) Bagaimanakah metode pendidikan karakter menurut Al-Ghazali dalam kitab Ayyuhā al-walad.Penelitian ini merupakan penelitian kepustakaan (library research), dengan obyek penelitian kitab Ayyuhal-Walad dan didukung oleh beberapa buku lain. Pendekatan penelitian yang digunakan adalah pendekatan filosofis. Sedangkan analisis data menggunakan analisis isi (content analysis). Dengan fokus kajian yang dibahas dalam penelitian ini adalah konsep pendidikan karakter menurut al-Ghazali dalam kitab ayyuhal-walad.